Motivation and attitudes towards learning English: A study of international undergraduates in Malaysia / Gao Yanchao - Gao , Yanchao (2011)
It has been proven that attitudes and motivation are important for a learner in second language learning. This study explores the attitudes and motivation of international undergraduates who are non-native English speakers towards learning English in universities of Malaysia. 64 undergraduates from three different universities in Malaysia are chosen as participants. Gardner's Socio-education Model (2005) is used as the framework in this study. The use of questionnaire as an instrument in this study was adapted from Gardner's AMTB (2005). The questionnaire is used to elicit undergraduates' information and to obtain their responses towards learning English in Malaysia. In this analysis, the researcher desires to clarify the relationship among a number of motivational factors. There are three objectives in this study. The first objective is to study international university students' Attitudes towards learning English in Malaysia. The second is to determine the motivational factors that affect international university undergraduates towards learning English in Malaysia. The third is to study whether there are significant differences among the participants' responses towards learning English in Malaysia. The findings showed that students were more integratively and instrumentally orientated in learning English. They held a strong desire and good Attitudes towards Learning English. The findings also revealed that students' attitudes and motivation differed by factors of university, gender, years of study and regions they were from.